Molecular Tectonics: A Node‐and‐Linker Building Block Approach to a Family of Hydrogen‐Bonded Frameworks. Issue 42 (3rd July 2019) - Boer, Stephanie A.; Morshedi, Mahbod; Tarzia, Andrew; Doonan, Christian J.; White, Nicholas G.
Abstract: While numerous hydrogen‐bonded organic frameworks (HOFs) have been reported, typically these cannot be prepared predictably or in a modular fashion. In this work, we report a family of nine diamondoid crystalline porous frameworks assembled via hydrogen bonding between poly‐amidinium and poly‐carboxylate tectons. The frameworks are prepared at room temperature in either water or water/alcohol mixtures. Importantly, both the cationic and anionic components can be varied and additional functionality can be incorporated into the frameworks, which show good stability including to prolonged heating in DMSO or water. Abstract : Predictable HOF synthesis : The node‐and‐linker assembly of amidinium and carboxylate tectons gives nine diamondoid open, crystalline hydrogen bonded frameworks in a predictable manner.